Improving Capacity Utilisation in Bread Processing Factories Using the BLOCPLAN Algorithm (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2024)
Numerous factors are causing small and medium enterprises (SMEs) to close at an alarming rate worldwide. The faulty manufacturing and management setup made the system costly and wasteful.  Detailed research into the causes of these collapses made the factory layout issue important to this study. This research aims to examine the current floor plans for bakeries to increase capacity utilization, enhance the production efficiency for the firms, and increase profit using the BLOCPLAN (Block Layout Overview with Layout Planning) algorithm software. Measured and recorded were the rectilinear distances between the manufacturing workstations at three bakeries situated in Warri, Nigeria. This was achieved by closely monitoring the production process and using a stopwatch. The initial production area was determined in square metres by measuring and recording the length and width of the manufacturing equipment. The rectilinear distances for Bakery A, B, and C are 13.9, 17.4, and 21.1 metres, respectively, based on measurements. For bakeries A, B, and C, the associated production throughput times were 48 minutes, 76 minutes, and 81.5 minutes, respectively. 987.92 m2, 1,088.46 m2, and 786.434 m2 make up the combined production areas of bakeries A, B, and C. Using the BLOCPLAN, 20 iterations were carried out at each bakery, and the iteration with the best R-score for each bakery was deployed as the best alternative layout. The R-Score results were 0.81, 0.64, and 0.91 for bakeries A, B, and C respectively. As a result, the effectiveness of bakeries A, B, and C received a boost of 58.3%, 52.8%, and 67.3%. The results obtained from this work show that optimizing the facility layout of a typical bread production factory using the BLOCPLAN technique could increase production capacity and improve overall system performance.
Keywords: Activity Relationship Chart, BLOCPLAN, Factory Layout, Optimization